2011
DOI: 10.1002/jctb.2654
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic organosolv fractionation of willow wood and wheat straw as pretreatment for enzymatic cellulose hydrolysis

Abstract: BACKGROUND: Ethanol-based organosolv fractionation of lignocellulosic biomass is an effective pretreatment technology for enzymatic cellulose hydrolysis to produce sugars and lignin within a biorefinery. This study focuses on the catalytic effect of H 2 SO 4 , HCl, and MgCl 2 on organosolv pretreatment of willow wood and wheat straw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 31 publications
6
78
0
Order By: Relevance
“…Since most organic solvents (except organic acids) are too mild to destroy the linkages and structure of lignocellulosic materials, organosolv process with the assistance of various catalysts (acids, salts, and alkalis) is usually recommended to pretreat different lignocellulosic materials (Huijgen et al, 2011;Park et al, 2010). Huijgen et al (2011) investigated the organosolv process of willow wood and wheat straw in ethanol under the catalysis of H 2 SO 4 , HCl, and MgCl 2 .…”
Section: Organosolv Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most organic solvents (except organic acids) are too mild to destroy the linkages and structure of lignocellulosic materials, organosolv process with the assistance of various catalysts (acids, salts, and alkalis) is usually recommended to pretreat different lignocellulosic materials (Huijgen et al, 2011;Park et al, 2010). Huijgen et al (2011) investigated the organosolv process of willow wood and wheat straw in ethanol under the catalysis of H 2 SO 4 , HCl, and MgCl 2 .…”
Section: Organosolv Processmentioning
confidence: 99%
“…Huijgen et al (2011) investigated the organosolv process of willow wood and wheat straw in ethanol under the catalysis of H 2 SO 4 , HCl, and MgCl 2 . It was reported that the addition of catalysts improved the fractionation of both willow wood and wheat straw.…”
Section: Organosolv Processmentioning
confidence: 99%
“…It is also worth noting the high hemicellulose elimination (78 %) found during organosolv pretreatment in this work, which is larger than the hemicellulose removal described elsewhere, (around 11–19 % and 34 %, respectively) using different elm clones. Slightly lower values (72 %) were described by Pan et al., who subjected poplar to organosolv pretreatment, while Huijgen et al . found higher hemicellulose removal (around 97 %) with willow wood and wheat straw, although using more severe conditions.…”
Section: Resultsmentioning
confidence: 85%
“…The value of 49 % is higher as compared to other studies, using different elm clones, where a lignin removal of 27–42 % was described using the same pretreatment conditions but with higher ethanol concentration (75 % v/v). Higher delignification degrees compared to elm wood have been reached with other lignocellulosic materials such as willow wood (59 %), wheat straw (74 %) and poplar (74 %) although using more severe conditions ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation